Biomimetic Nanovaccines: A Novel Approach in Immunization - Khojini, Javad Y.; Babaei, Benjamin; Shakarami, Maryam; Mofidi, Mahdis; Tahershamsi, Zahra; Arjmand, Tahura Fayeghi; Tajbakhsh, Amir; Gheibihayat, Seyed Mohammad (Current Pharmaceutical Design, 2023)
As the World Health Organization (WHO) declared, vaccines prevent an average of 2-3 million deaths yearly from diseases. However, effective prophylactic and therapeutic vaccines have yet to be developed for eradicating the deadliest diseases, viz., types of cancer, malaria, human immunodeficiency virus (HIV), and most serious microbial infections. Furthermore, scores of the existing vaccines have disadvantages, such as failure to completely stimulate the immune system, in vivo instability, high toxicity, need for the cold chain, and multiple administrations. Thus, good vaccine candidates need to be designed to elicit adaptive immune responses. In this line, the integration of sciences along with the use of various technologies has led to the emergence of a new field in vaccine production called biomimetic nanovaccines (BNVs). Given that, nanotechnology can significantly contribute to the design of such vaccines, providing them with enhanced specificity and potency. Nanoparticles (NPs) and biomimetic NPs (BNPs) are now exploited as the main carriers for drug delivery systems, especially BNPs, whose biological mimicry makes them escape the immune system and transport drugs to the desired target. The drug accordingly seeks to camouflage itself with the help of NPs and the membranes taken from cells in the human body, including red blood cells (RBCs), white blood cells (WBCs), platelets, and cancer cells, for more effective and ideal delivery. As BNPs have recently become the center of attention in vaccine design, this review deliberates on the advances in BNVs.
Keywords: nano-based drug delivery system